Aliphatic amphiphilic dendritic polyester as well as preparation method and application thereof
By adopting aliphatic amphiphilic dendritic polyester and using the ring-opening nucleation polymerization process of high-functional polyols and acid anhydride compounds, the problem of difficult automobile coatings to meet the rapid drying and excellent appearance at the same time is solved, and the low polyester is achieved Viscosity, high solids content and excellent chemical resistance.
Patent Information
- Application Number
- CN202411212314.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2025-02-07
AI Technical Summary
Existing automotive coatings are difficult to meet the requirements of rapid drying and excellent appearance at the same time, resulting in poor coating performance.
Aliphatic amphiphilic dendritic polyester is used to prepare a polyester with a compact structure and amphiphilicity through a ring-opening nucleation polymerization process of high-functional polyols and acid anhydrides.
The polyester has low viscosity, high solids content, excellent chemical media resistance and the effect of fast drying and excellent appearance are achieved.
Smart Images

Figure BDA0005020609970000151 
Figure BDA0005020609970000161 
Figure BDA0005020609970000181
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of coating resins, and in particular relates to an aliphatic amphiphilic dendritic polyester. The present invention further relates to a preparation method of the aliphatic amphiphilic dendritic polyester and its application in automobile varnish. Background Art
[0002] With the rapid development of social economy, the per capita car ownership in my country continues to grow, and the demand for various automotive products has also increased. In the field of automotive coatings, automotive coatings not only give the car body excellent visual effects, but also serve as a protective barrier to effectively resist corrosion from various external chemical media. Among them, the car's clear coat layer is the first barrier to resist external erosion and is of great significance to improving the vehicle's resistance to chemical media.
[0003] In the application of automotive coatings, especially in the field of automotive refinishing, clearcoats are required to not only have excellent appearance, but also have a faster drying speed. However, current automotive coatings often cannot meet the requirements of fast drying and excellent appearance at the same time. Generally speaking, if the drying speed of the coating is too fast, the leveling of the coating will be affected, resulting in poor gloss and fullness, thus affecting the final appearance; on the contrary, in order to obtain a good appearance, a longer leveling time is usually required, which in turn leads to a significant reduction in drying speed, affecting construction efficiency.
[0004] In order to solve this technical problem, researchers usually improve the performance of coatings by optimizing the combination of resins, curing agents, catalysts and solvents. Generally speaking, the chemical resistance of the coating is closely related to the cross-linking density of the resin, and the resin needs to have good leveling properties to achieve excellent appearance. At the same time, rapid drying requires the resin to have a multi-functional macromolecular structure. Therefore, the use of compact macromolecules, such as hyperbranched or dendritic compounds, has become an effective way to improve the performance of coatings.
[0005] Dendrimers are a type of nonlinear polymer with a highly branched structure and a large number of modifiable end groups. By controlling and designing the size, shape, structure and functional elements of the molecules at the molecular level, they can obtain special properties that traditional linear polymers do not have. However, traditional dendrimers have the following defects in practical applications: (1) They are usually prepared using AB2 or AB3 branched structural units, but the polymerization process is difficult to fully control, which easily increases the radius of the polymer, resulting in a loose structure, which manifests as low solid content and high viscosity, affecting the coating performance; (2) Traditional dendrimers have low acid values and high hydroxyl values, resulting in a lack of water solubility. They need to be dissolved in organic solvents before mixing and use, which limits their application in water-based coatings.
[0006] The above problems severely limit the widespread application of dendritic polymers in the field of automotive coatings. Therefore, it is urgent to develop new dendritic polymers that can simultaneously meet the requirements of fast drying and excellent appearance effects and expand their application in water-based coatings. Summary of the invention
[0007] The invention provides an aliphatic amphiphilic dendritic polyester and a preparation method thereof and application thereof in automobile varnish. The provided aliphatic amphiphilic dendritic polyester can simultaneously meet the requirements of rapid drying and excellent appearance effect.
[0008] The technical solution of the present invention is as follows:
[0009] An aliphatic amphiphilic dendritic polyester, the polyester comprising 60-100 parts by weight of polyester polyol and 0-40 parts by weight of solvent, wherein the polyester polyol comprises the following chain segments:
[0010] A first segment provided by a high-functionality polyol component I;
[0011] A second segment provided by an anhydride compound;
[0012] A third segment provided by a polyol component II having a molecular weight <500;
[0013] in,
[0014] The OH value of the polyester polyol is ≥115KOHmg / g;
[0015] The acid value of the polyester polyol is greater than or equal to 50KOHmg / g and less than or equal to 290KOHmg / g;
[0016] The molar ratio of the acid anhydride compound to the high-functionality polyol component I is 3-6, wherein the average functionality of the high-functionality polyol component I is greater than or equal to 3.
[0017] In the present invention, the OH value of the polyester polyol is measured according to ISO 4629-3. The acid value of the polyester polyol is measured according to GB / T 6743.
[0018] The structure of the polyester polyol is spherical, wherein the first segment is the center of the sphere, the second segment is the core of the sphere, and the third segment is the shell of the sphere.
[0019] The hydroxyl value of the polyester polyol is limited to greater than 115 in the present invention, which can achieve the technical effect of improving the resistance of the coating.
[0020] The present invention limits the molecular weight of the polyol component II to less than 500 because too high a molecular weight will lead to an increase in resin viscosity and fail to achieve the technical effect of high solid and low viscosity.
[0021] In the present invention, the functionality of the polyol component II is 2 or more.
[0022] The present invention limits the acid value of the polyester polyol, and an appropriate acid value gives the polyester excellent hydrophilicity.
[0023] In the embodiment of the present invention, based on 100 parts by weight of the total aliphatic amphiphilic dendritic polyester, the content of the solvent is 0-40 parts, the content of the polyester polyol is 60-100 parts, and the content of the high-functionality polyol component I is 6-22 parts, the content of the acid anhydride compound is 28-67 parts, and the content of the polyol component II with a molecular weight <500 is 13-53 parts. The contents here all refer to weight content.
[0024] In some embodiments of the present invention, the high-functionality polyol component I is selected from at least one of sorbitol, pentaerythritol, xylitol, maltitol, inositol, mannitol, glucose, trimethylolpropane, trimethylolethane, glycerol, arabitol, trimethylolaminomethane, triethanolamine, and β-hydroxyalkylamide.
[0025] In some embodiments of the present invention, the acid anhydride compound is selected from at least one of hexahydrophthalic anhydride, acetic anhydride, succinic anhydride, maleic anhydride, isophthalic anhydride, trichloroacetic anhydride, trifluoroacetic anhydride, adipic anhydride, tetrahydrophthalic anhydride and maleic anhydride.
[0026] In some embodiments of the present invention, the polyol component II with a molecular weight of <500 is selected from at least one of sorbitol, pentaerythritol, xylitol, maltitol, inositol, mannitol, glucose, trimethylolpropane, trimethylolethane, glycerol, arabitol, trimethylolaminomethane, triethanolamine, ethylene glycol, propylene glycol, butylene glycol, dimethyl-1,3-propanediol, neopentyl glycol, 2-butyl-2-ethyl-1,3-propanediol, 3-hydroxy-2,2-dimethyl-3-hydroxy-2,2-dimethylpropyl propionate, 1,4-cyclohexanedimethanol, trimethylpentanediol, HAA_β-hydroxyalkylamide, isosorbide, 1,2,6-hexanetriol, and hydrogenated bisphenol A.
[0027] The solvent may be selected from at least one of butyl acetate, xylene, dipropylene glycol methyl ether, propylene glycol methyl ether acetate, propylene glycol methyl ether, 1,3,5-trimethylbenzene, and 1,2,4-trimethylbenzene.
[0028] The present invention also provides a method for preparing the aforementioned aliphatic amphiphilic dendritic polyester, the method comprising the following steps:
[0029] 1) Add the high-functionality polyol component I into the reaction device, slowly heat up to 100-130° C., and stir for 0.5-2 hours;
[0030] 2) adding the acid anhydride compound to the reaction solution prepared in step 1) in a dropwise manner, and then slowly heating to 120-160° C. for reaction, and testing the acid value at predetermined time intervals until the theoretical acid value is reached;
[0031] 3) adding the polyol component II with a molecular weight of less than 500 to the reaction solution prepared in step 2), and after the addition, heating the mixture to 150-200° C. at a rate of 8-12° C. / hour and maintaining the temperature, and testing the acid value at predetermined intervals until the target acid value is reached;
[0032] 4) cooling the reaction solution prepared in step 3) to 100-120° C. and dehydrating the solution at a vacuum pressure of -0.05 to -0.1 MPa for 0.5 to 2 hours;
[0033] 5) Cooling the reaction solution prepared in step 4) to 80-110° C., adding 0-40 parts by weight of the solvent, stirring evenly, cooling to below 70-90° C., and filtering the material.
[0034] The slow heating in steps 1) and 2) may refer to completing the heating in a time greater than or equal to 1 hour to avoid explosion.
[0035] Wherein, the solvent is selected from at least one of butyl acetate, xylene, dipropylene glycol methyl ether, propylene glycol methyl ether acetate, propylene glycol methyl ether, 1,3,5-trimethylbenzene, and 1,2,4-trimethylbenzene.
[0036] In the above method, the acid value is tested in accordance with GB / T 6743.
[0037] In the above step 3), after the addition of the polyol component II is completed, the temperature is raised to 150-200° C. at a rate of 10° C. / hour and kept warm.
[0038] In the above steps 2) and 3), the predetermined time interval is 1 hour.
[0039] In the above method, the reaction device can be a stirring device equipped with a stirrer and a thermometer.
[0040] In the above method, the theoretical acid value is calculated by the following method: ((amount of anhydride compound substance*functionality-high-functionality polyol component I*functionality))*56100 / (mass of anhydride compound+mass of high-functionality polyol component I).
[0041] In the above method, the target acid value is greater than or equal to 50 KOH mg / g and less than or equal to 290 KOH mg / g.
[0042] The present invention also provides an automobile clear coat, which comprises any of the above-mentioned aliphatic amphiphilic dendritic polyesters.
[0043] Compared with the prior art, the present invention has the following beneficial effects:
[0044] 1. The product has lower viscosity and higher solid content: The aliphatic amphiphilic dendritic polyester proposed in the present invention optimizes the molecular structure by selecting more flexible aliphatic raw materials, obtains a more compact polymerization structure by the ring-opening nucleation method of acid anhydride and high-functionality polyol, realizes the minimization of the polymer on a two-dimensional scale, significantly reduces the viscosity of the polyester, and increases the solid content, which is superior to the polyester products in the prior art.
[0045] 2. Realizing the amphiphilicity of resinous polyester: The aliphatic amphiphilic dendritic polyester in the present invention realizes the amphiphilicity of polyester by introducing specific carboxylic acids (i.e., acid anhydrides) and polyols. It is suitable for both oily coating systems and water-based coating systems, thus expanding the application range of polyester. It has significant advantages over the dendritic polyester in the prior art.
[0046] 3. Improving the chemical resistance of automobile varnish: The aliphatic amphiphilic dendritic polyester in the present invention adopts a precisely controlled polymerization process (including the selection of temperature in each step of the reaction, the control of the dripping of acid anhydride, the control of the target acid value, etc.), which improves the structural compactness and cross-linking density of the polyester, thereby significantly improving the chemical resistance of the automobile varnish, which is better than the existing polyester products.
[0047] 4. Improving the incompatibility between appearance and drying speed: The present invention improves the degree of branching and introduces a large number of hydroxyl groups by selecting raw materials (selecting high-functionality polyols) and coordinating with processes (capping high-functionality polyols with anhydrides and then grafting polyols in the process), thereby improving the leveling and glossiness of the automotive coating while ensuring a fast drying speed, solving the contradiction between the appearance and drying speed of automotive coatings in the prior art and providing a more balanced coating effect.
[0048] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. DETAILED DESCRIPTION
[0049] The present invention provides an aliphatic amphiphilic dendritic polyester, wherein the polyester comprises 60-100 parts by weight of polyester polyol and 0-40 parts by weight of solvent, wherein the polyester polyol comprises the following chain segments:
[0050] A first segment provided by a high-functionality polyol component I;
[0051] A second segment provided by an anhydride compound;
[0052] A third segment provided by a polyol component II having a molecular weight <500;
[0053] in,
[0054] The OH value of the polyester polyol is ≥115KOHmg / g;
[0055] The acid value of the polyester polyol is greater than or equal to 50KOHmg / g and less than or equal to 290KOHmg / g;
[0056] The molar ratio of the acid anhydride compound to the high-functionality polyol component I is 3-6, wherein the average functionality of the high-functionality polyol component I is greater than or equal to 3.
[0057] In the present invention, the OH value of the polyester polyol is measured according to ISO 4629-3. The acid value of the polyester polyol is measured according to GB / T 6743.
[0058] The structure of the polyester polyol of the present invention is spherical, wherein the first chain segment is the center of the sphere, the second chain segment is the core of the sphere, and the third chain segment is the shell of the sphere.
[0059] In the present invention, the functionality of the polyol component II is 2 or more.
[0060] In the embodiment of the present invention, based on 100 parts by weight of the total aliphatic amphiphilic dendritic polyester, the content of the solvent is 0-40 parts, the content of the polyester polyol is 60-100 parts, and the content of the high-functionality polyol component I is 6-22 parts, the content of the acid anhydride compound is 28-67 parts, and the content of the polyol component II with a molecular weight <500 is 13-53 parts. The contents here all refer to weight content.
[0061] In some embodiments of the present invention, the high-functionality polyol component I is selected from at least one of sorbitol, pentaerythritol, xylitol, maltitol, inositol, mannitol, glucose, trimethylolpropane, trimethylolethane, glycerol, arabitol, trimethylolaminomethane, triethanolamine, and β-hydroxyalkylamide.
[0062] In some embodiments of the present invention, the acid anhydride compound is selected from at least one of hexahydrophthalic anhydride, acetic anhydride, succinic anhydride, maleic anhydride, isophthalic anhydride, trichloroacetic anhydride, trifluoroacetic anhydride, adipic anhydride, tetrahydrophthalic anhydride and maleic anhydride.
[0063] In some embodiments of the present invention, the polyol component II with a molecular weight of <500 is selected from at least one of sorbitol, pentaerythritol, xylitol, maltitol, inositol, mannitol, glucose, trimethylolpropane, trimethylolethane, glycerol, arabitol, trimethylolaminomethane, triethanolamine, ethylene glycol, propylene glycol, butylene glycol, dimethyl-1,3-propanediol, neopentyl glycol, 2-butyl-2-ethyl-1,3-propanediol, 3-hydroxy-2,2-dimethyl-3-hydroxy-2,2-dimethylpropyl propionate, 1,4-cyclohexanedimethanol, trimethylpentanediol, HAA_β-hydroxyalkylamide, isosorbide, 1,2,6-hexanetriol, and hydrogenated bisphenol A.
[0064] The solvent may be selected from at least one of butyl acetate, xylene, dipropylene glycol methyl ether, propylene glycol methyl ether acetate, propylene glycol methyl ether, 1,3,5-trimethylbenzene, and 1,2,4-trimethylbenzene.
[0065] The present invention also provides a method for preparing the aforementioned aliphatic amphiphilic dendritic polyester, the method comprising the following steps:
[0066] 1) Add the high-functionality polyol component I into the reaction device, slowly heat up to 100-130° C., and stir for 0.5-2 hours;
[0067] 2) adding the acid anhydride compound to the reaction solution prepared in step 1) in a dropwise manner, and then slowly heating to 120-160° C. for reaction, and testing the acid value at predetermined time intervals until the theoretical acid value is reached;
[0068] 3) adding the polyol component II with a molecular weight of less than 500 to the reaction solution prepared in step 2), and after the addition, heating the mixture to 150-200° C. at a rate of 8-12° C. / hour and maintaining the temperature, and testing the acid value at predetermined intervals until the target acid value is reached;
[0069] 4) cooling the reaction solution prepared in step 3) to 100-120° C. and dehydrating the solution at a vacuum pressure of -0.05 to -0.1 MPa for 0.5 to 2 hours;
[0070] 5) Cooling the reaction solution prepared in step 4) to 80-110° C., adding 0-40 parts by weight of the solvent, stirring evenly, cooling to below 70-90° C., and filtering the material.
[0071] Compared with traditional dendritic polyester, the present invention has the following characteristics:
[0072] (1) Reduce the viscosity of dendritic polyester and increase the solid content
[0073] The traditional dendritic polyester polymerization process is uncontrollable, resulting in longer linear molecular chains, larger polymer radius sizes, and loose structures, thus exhibiting the characteristics of high viscosity and low solid content.
[0074] The present invention uses aliphatic raw materials to make the polyester structure more flexible, thereby effectively reducing the viscosity. In addition, the present invention adopts a polymerization process of ring-opening nucleation of anhydride and high-functionality polyol, which reduces the occurrence of side reactions, forms a more compact molecular structure, reduces the molecular radius, and achieves lower viscosity and higher solid content.
[0075] (2) Enhance the amphiphilicity of dendritic polyesters
[0076] Traditional dendritic polyesters have strong lipophilicity but poor hydrophilicity due to their low acid value, high hydroxyl value and high degree of branching, which limits their application in water-based coatings.
[0077] The present invention introduces a certain proportion of carboxylic acid, and the neutralized carboxylate radical can make the dendritic polyester hydrophilic, so that the polyester has both lipophilicity and hydrophilicity, ensuring that it can be used in both oily and water-based coatings, thus broadening its application range.
[0078] (3) Improve the chemical resistance of automotive clearcoat
[0079] Currently, conventional automotive varnishes have insufficient resistance to chemical media such as engine oil, gasoline, acid, alkali, and water, which affects the service life and durability of the coating.
[0080] The present invention adopts a polymerization process of ring-opening nucleation of anhydride and high-functionality polyol to make the polymer structure controllable, thereby obtaining a more compact branched structure and a higher hydroxyl value, thereby increasing the crosslinking density and significantly improving the chemical resistance of the automobile varnish.
[0081] (4) Considering both the appearance and drying speed of automotive clearcoat
[0082] Currently, conventional automotive varnishes often find it difficult to have both fast drying speed and excellent appearance. Fast drying will lead to poor leveling, low gloss and fullness, while coatings with excellent appearance often require a longer leveling time.
[0083] The present invention reduces the viscosity of polyester by using a polymerization process of aliphatic raw materials and acid anhydride and high-functionality polyol ring-opening nucleation, thereby improving the leveling property of the coating. At the same time, by increasing the branching degree and introducing a large number of hydroxyl groups, the drying speed of the coating is increased, thereby achieving a more excellent coating appearance under the premise of ensuring rapid drying.
[0084] In this article, the range expressed by "a value to another value" is a summary expression method to avoid listing all the values in the range one by one in the specification. Therefore, the description of a specific numerical range covers any value in the numerical range and a smaller numerical range defined by any value in the numerical range, just as if the arbitrary value and the smaller numerical range were explicitly written in the specification.
[0085] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of protection of the present invention. In practical applications, improvements and adjustments made by technicians according to the present invention still belong to the scope of protection of the present invention.
[0086] In the following Examples 1-10, the total mass content of the produced aliphatic amphiphilic dendritic polyester is taken as 100 parts.
[0087] Example 1
[0088] Add pentaerythritol (polyol component I with high functionality, 8.15 parts by mass) to a reactor equipped with a stirrer and a thermometer, slowly heat up to 110°C, and keep at 110±2°C for 0.5h; after the insulation is completed, add hexahydrophthalic anhydride (anhydride compound, 37.4 parts by mass) to the reaction solution in a dropwise manner, slowly heat up to 140±2°C and keep warm, test the acid value every 1 hour according to GB / T 6743, and the reaction is qualified after the theoretical acid value is reached (theoretical acid value: 290-300mgKOH / g). After the acid value is qualified, add pentaerythritol (polyol component II with molecular weight <500, 24.45 parts by mass) to the reactor; then gradually heat up to 170±2°C at 10°C / hour and keep warm, and test the acid value every 1 hour according to GB / T6743 until the target acid value is reached, which is 50-55mgKOH / g. After the acid value is qualified, the temperature is lowered to 115±2°C, and dehydration is performed for 2 hours using a vacuum pressure of -0.05 to -0.1Mpa. After completion, the temperature is lowered to 115±2°C, butyl acetate (solvent, 30 parts by weight) is added, stirred evenly, and then the temperature is lowered to below 70°C, and the material is filtered out. The aliphatic amphiphilic dendritic polyester is obtained.
[0089] Example 2
[0090] Add glycerol (polyol component I with high functionality, 8.66 parts by mass) to a reactor equipped with a stirrer and a thermometer, slowly heat up to 110°C, and keep at 110±2°C for 0.5h; after the insulation is completed, add hexahydrophthalic anhydride (anhydride compound, 44.03 parts by mass) to the reaction solution in a dropwise manner, slowly heat up to 140±2°C and keep warm, test the acid value every 1 hour according to GB / T 6743, and the reaction is qualified after the theoretical acid value is reached (theoretical acid value: 200-210mgKOH / g). After the acid value is qualified, add glycerol (polyol component II with molecular weight <500, 17.31 parts by mass) to the reactor; then gradually heat up to 170±2°C at 10°C / hour and keep warm, and test the acid value every 1 hour according to GB / T 6743 until the target acid value is reached, which is 52-57mgKOH / g. After the acid value is qualified, the temperature is lowered to 115±2°C, and dehydration is performed for 2 hours using a vacuum pressure of -0.05 to -0.1Mpa. After completion, the temperature is lowered to 90±2°C, butyl acetate (solvent, 30 parts by weight) is added, stirred evenly, and then the temperature is lowered to below 70°C, and the material is filtered out. The aliphatic amphiphilic dendritic polyester is obtained.
[0091] Example 3
[0092] Add pentaerythritol (polyol component I with high functionality, 8.25 parts by mass) to a reactor equipped with a stirrer and a thermometer, slowly heat up to 110°C, and keep at 110±2°C for 0.5h; after the insulation is completed, add tetrahydrophthalic anhydride (anhydride compound, 37.37 parts by mass) to the reaction solution in a dropwise manner, slowly heat up to 140±2°C and keep warm, test the acid value every 1 hour according to GB / T 6743, and the reaction is qualified after the theoretical acid value is reached (theoretical acid value: 298-308mgKOH / g). After the acid value is qualified, add trimethylolpropane (polyol component II with molecular weight <500, 24.38 parts by mass) to the reactor; then gradually heat up to 170±2°C at 10°C / hour and keep warm, and test the acid value every 1 hour according to GB / T6743 until the target acid value is reached, which is 51-56mgKOH / g. After the acid value is qualified, the temperature is lowered to 115±2°C, and dehydration is performed for 2 hours using a vacuum pressure of -0.05 to -0.1Mpa. After completion, the temperature is lowered to 105±2°C, xylene (solvent, 15 parts by weight) and butyl acetate (solvent, 15 parts by weight) are added, stirred evenly, and then the temperature is lowered to below 70°C, and the material is filtered out. The aliphatic amphiphilic dendritic polyester is obtained.
[0093] Example 4
[0094] Add pentaerythritol (polyol component I with high functionality, 6.53 parts by mass) to a reaction kettle equipped with a stirrer and a thermometer, slowly heat up to 110°C, and keep at 110±2°C for 0.5h; after the insulation is completed, add tetrahydrophthalic anhydride (anhydride compound, 43.85 parts by mass) to the reaction solution in a dropwise manner, slowly heat up to 140±2°C and keep warm, test the acid value every 1 hour according to GB / T 6743, and the reaction is qualified after the theoretical acid value is reached (theoretical acid value: 428-438mgKOH / g). After the acid value is qualified, add pentaerythritol (polyol component II with molecular weight <500, 19.62 parts by mass) to the reaction kettle; then gradually heat up to 170±2°C at 10°C / hour and keep warm, and test the acid value every 1 hour according to GB / T6743 until the target acid value is reached, which is 200-205mgKOH / g. After the acid value is qualified, the temperature is lowered to 115±2°C, and dehydration is performed for 2 hours using a vacuum pressure of -0.05 to -0.1Mpa. After completion, the temperature is lowered to 90±2°C, butyl acetate (solvent, 30 parts by weight) is added, stirred evenly, and then the temperature is lowered to below 70°C, and the material is filtered out. The aliphatic amphiphilic dendritic polyester is obtained.
[0095] Example 5
[0096] Trimethylolpropane (high-functionality polyol component I, 9.40 parts by mass) was added to a reaction kettle equipped with a stirrer and a thermometer, and the temperature was slowly raised to 110° C. and maintained at 110±2° C. for 0.5 h. After the insulation was completed, tetrahydrophthalic anhydride (anhydride compound, 31.98 parts by mass) was added dropwise to the reaction solution. After completion, the temperature was slowly raised to 140±2° C. and maintained. The acid value was tested according to GB / T 6743 every 1 hour. The reaction was qualified after the theoretical acid value was reached (theoretical acid value: 285-295 mgKOH / g). After the acid value is qualified, add 3-hydroxy-2,2-dimethyl-3-hydroxy-2,2-dimethylpropyl propionate (polyol component II with molecular weight <500, mass content 28.62 parts) to the reactor; then gradually increase the temperature to 170±2℃ at 10℃ / hour and keep warm, and test the acid value according to GB / T 6743 every 1 hour until the target acid value is reached, the target acid value is 58-63mgKOH / g. After the acid value is qualified, cool down to 115±2℃, and use vacuum pressure -0.05~-0.1Mpa for dehydration for 2 hours. After completion, cool down to 90±2℃, add butyl acetate (solvent, mass content 30 parts), stir evenly, cool down to below 70℃, and filter out the material. Obtain aliphatic amphiphilic dendritic polyester.
[0097] Example 6
[0098] Add pentaerythritol (polyol component I with high functionality, 10.17 parts by mass) to a reaction kettle equipped with a stirrer and a thermometer, slowly heat up to 110°C, and keep at 110±2°C for 0.5h; after the insulation is completed, add maleic anhydride (anhydride compound, 29.31 parts by mass) to the reaction solution in a dropwise manner, slowly heat up to 140±2°C and keep warm, test the acid value every 1 hour according to GB / T 6743, and the reaction is qualified after the theoretical acid value is reached (theoretical acid value: 425-435mgKOH / g). After the acid value is qualified, add pentaerythritol (polyol component II with molecular weight <500, 30.52 parts by mass) to the reaction kettle; then gradually heat up to 170±2°C at 10°C / hour and keep warm, and test the acid value every 1 hour according to GB / T6743 until the target acid value is reached, which is 64-69mgKOH / g. After the acid value is qualified, the temperature is lowered to 115±2°C, and dehydration is performed for 2 hours using a vacuum pressure of -0.05 to -0.1Mpa. After completion, the temperature is lowered to 90±2°C, butyl acetate (solvent, 30 parts by weight) is added, stirred evenly, and then the temperature is lowered to below 70°C, and the material is filtered out. The aliphatic amphiphilic dendritic polyester is obtained.
[0099] Example 7
[0100] Add pentaerythritol (polyol component I with high functionality, 20.48 parts by mass) to a reaction kettle equipped with a stirrer and a thermometer, slowly heat up to 110°C, and keep at 110±2°C for 0.5h; after the insulation is completed, add maleic anhydride (anhydride compound, 59.04 parts by mass) to the reaction solution in a dropwise manner, slowly heat up to 140±2°C and keep warm, test the acid value every 1 hour according to GB / T 6743, and the reaction is qualified after the theoretical acid value is reached (theoretical acid value: 425-435mgKOH / g). After the acid value is qualified, add pentaerythritol (polyol component II with molecular weight <500, 20.48 parts by mass) to the reaction kettle; then gradually heat up to 170±2°C at 10°C / hour and keep warm, and test the acid value every 1 hour according to GB / T6743 until the target acid value is reached, which is 261-266mgKOH / g. After the acid value is qualified, the temperature is lowered to 115±2°C, and dehydration is performed for 2 hours using a vacuum pressure of -0.05 to -0.1 MPa. After completion, the temperature is lowered to below 90°C, and the material is filtered out to obtain an aliphatic amphiphilic dendritic polyester.
[0101] Example 8
[0102] Add glycerol (polyol component I with high functionality, 20.54 parts by mass) to a reactor equipped with a stirrer and a thermometer, slowly heat up to 110°C, and keep at 110±2°C for 0.5h; after the insulation is completed, add maleic anhydride (anhydride compound, 65.63 parts by mass) to the reaction solution in a dropwise manner, slowly heat up to 140±2°C and keep warm, test the acid value every 1 hour according to GB / T 6743, and the reaction is qualified after the theoretical acid value is reached (theoretical acid value: 436-446mgKOH / g). After the acid value is qualified, add ethylene glycol (polyol component II with molecular weight <500, 13.83 parts by mass) to the reactor; then gradually heat up to 170±2°C at 10°C / hour and keep warm, and test the acid value every 1 hour according to GB / T 6743 until the target acid value is reached, which is 261-266mgKOH / g. After the acid value is qualified, the temperature is lowered to 115±2°C, and dehydration is performed for 2 hours using a vacuum pressure of -0.05 to -0.1 MPa. After completion, the temperature is lowered to below 90°C, and the material is filtered out to obtain an aliphatic amphiphilic dendritic polyester.
[0103] Example 9
[0104] Add glycerol (polyol component I with high functionality, 6.67 parts by mass) to a reactor equipped with a stirrer and a thermometer, slowly heat up to 110°C, and keep at 110±2°C for 0.5h; after the insulation is completed, add hexahydrophthalic anhydride (anhydride compound, 33.91 parts by mass) to the reaction solution in a dropwise manner, slowly heat up to 140±2°C and keep warm, test the acid value every 1 hour according to GB / T 6743, and the reaction is qualified after the theoretical acid value is reached (theoretical acid value: 301-311 mgKOH / g). After the acid value is qualified, add trimethylolpropane (polyol component II with molecular weight <500, 19.42 parts by mass) to the reactor; then gradually heat up to 170±2°C at 10°C / hour and keep warm, and test the acid value every 1 hour according to GB / T 6743 until the target acid value is reached, which is 71-76 mgKOH / g. After the acid value is qualified, the temperature is lowered to 115±2°C, and dehydration is performed for 2 hours using a vacuum pressure of -0.05 to -0.1Mpa. After completion, the temperature is lowered to 90±2°C, butyl acetate (solvent, 30 parts by weight) is added, stirred evenly, and then the temperature is lowered to below 70°C, and the material is filtered out. The aliphatic amphiphilic dendritic polyester is obtained.
[0105] Example 10
[0106] Add glycerol (polyol component I with high functionality, 11.59 parts by mass) to a reaction kettle equipped with a stirrer and a thermometer, slowly heat up to 110°C, and keep at 110±2°C for 0.5h; after the insulation is completed, add maleic anhydride (anhydride compound, 37.03 parts by mass) to the reaction solution in a dropwise manner, slowly heat up to 140±2°C and keep warm, test the acid value every 1 hour according to GB / T 6743, and the reaction is qualified after the theoretical acid value is reached (theoretical acid value: 436-446mgKOH / g). After the acid value is qualified, add pentaerythritol (polyol component II with molecular weight <500, 51.38 parts by mass) to the reaction kettle; then gradually heat up to 170±2°C at 10°C / hour and keep warm, and test the acid value every 1 hour according to GB / T 6743 until the target acid value is reached, which is 76-81mgKOH / g. After the acid value is qualified, the temperature is lowered to 115±2°C, and dehydration is performed for 2 hours using a vacuum pressure of -0.05 to -0.1 MPa. After completion, the temperature is lowered to below 90°C, and the material is filtered out to obtain an aliphatic amphiphilic dendritic polyester.
[0107] Comparative Example 1
[0108] The difference from Example 1 is that the acid anhydride compound in Comparative Example 1 is an aromatic chemical raw material.
[0109] Add pentaerythritol (polyol component I with high functionality, 8.37 parts by mass) to a reactor equipped with a stirrer and a thermometer, slowly heat up to 110°C, and keep at 110±2°C for 0.5h; after the insulation is completed, add phthalic anhydride (anhydride compound, 35.48 parts by mass) to the reaction solution in a dropwise manner, slowly heat up to 140±2°C and keep warm, test the acid value every 1 hour according to GB / T 6743, and the reaction is qualified after the theoretical acid value is reached (theoretical acid value: 308-318mgKOH / g). After the acid value is qualified, add pentaerythritol (polyol component II with molecular weight <500, 25.14 parts by mass) to the reactor; then gradually heat up to 170±2°C at 10°C / hour and keep warm, and test the acid value every 1 hour according to GB / T 6743 until the target acid value is reached, which is 52-57mgKOH / g. After the acid value is qualified, the temperature is lowered to 115±2°C, and dehydration is performed for 2 hours using a vacuum pressure of -0.05 to -0.1Mpa. After completion, the temperature is lowered to 90±2°C, butyl acetate (solvent, 30 parts by weight) is added, stirred evenly, and then the temperature is lowered to below 70°C, and the material is filtered out to obtain a dendritic polyester.
[0110] Comparative Example 2
[0111] The difference from Example 2 is that the preparation method described in Comparative Example 2 adopts a traditional polymerization process.
[0112] Add hexahydrophthalic anhydride (anhydride compound, 44.03 parts by mass) to a reactor equipped with a stirrer and a thermometer, slowly heat to 110°C, and keep at 110±2°C for 0.5h; after the insulation is completed, add glycerol (high-functionality polyol component I, 25.97 parts by mass) to the reaction solution in a dropwise manner, slowly heat to 140±2°C and keep for 1 hour, then gradually heat to 170±2°C at 10°C / hour and keep. Test the acid value according to GB / T 6743 every 1 hour until the target acid value is reached, the target acid value is 79-84mgKOH / g. After the acid value is qualified, cool to 115±2°C, and use vacuum pressure -0.05~-0.1Mpa for dehydration for 2 hours. After completion, cool to 90±2°C, add butyl acetate (solvent, 30 parts by mass), stir evenly, cool to below 70°C, and filter out the material. Dendritic polyester is obtained.
[0113] Comparative Example 3
[0114] The difference from Example 3 is that the acid value of the dendritic polyester prepared in Comparative Example 3 is less than or equal to 10.
[0115] Add pentaerythritol (high-functionality polyol component I, 7.82 parts by mass) to a reactor equipped with a stirrer and a thermometer, slowly heat up to 110°C, and keep at 110±2°C for 0.5h; after the insulation is completed, add tetrahydrophthalic anhydride (anhydride compound, 35.46 parts by mass) to the reaction solution in a dropwise manner, slowly heat up to 140±2°C and keep warm, test the acid value every 1 hour according to GB / T 6743, and the reaction is qualified after the theoretical acid value is reached (theoretical acid value: 425-435mgKOH / g). After the acid value is qualified, add xylene (solvent, 15 parts by mass), trimethylolpropane (polyol component II with a molecular weight of <500, 23.14 parts by mass), and ethylene glycol (polyol component II with a molecular weight of <500, 3.56 parts by mass) to the reactor, and then gradually heat up to 170±2°C at 10°C / hour and keep warm. The acid value is tested every hour according to GB / T 6743 until the target acid value is reached, which is 0-10 mgKOH / g. After the acid value is qualified, the temperature is lowered to 105±2°C, butyl acetate (solvent, 15 parts by weight) is added, stirred evenly, the temperature is lowered to below 70°C, and the material is filtered out. Dendritic polyester is obtained.
[0116] The testing and characterization methods of the aliphatic amphiphilic dendritic polyesters prepared in Examples 1-10 and the dendritic polyesters prepared in Comparative Examples 1-3 are as follows:
[0117] (1) Appearance
[0118] The test was carried out in accordance with the national standard GB / T 8237.
[0119] (2) Solid content
[0120] The test was carried out in accordance with the national standard GB / T 1725. The test conditions were: temperature of 140°C, baking time of 60 min, and sample size of 1 g.
[0121] (3) Hydroxyl value
[0122] Tested in accordance with international standard ISO 4629-3.
[0123] (4) Acid value
[0124] The test was carried out in accordance with the national standard GB / T 6743.
[0125] (5) Viscosity
[0126] The test was carried out in accordance with the national standard GB / T 10247. The test conditions were: viscosity test temperature was 30°C and 80°C.
[0127] (6) Water solubility
[0128] The neutralization degree of the above Examples 1-10 and Comparative Examples 1-3 was calculated according to the polyester acid value, dimethylethanolamine was added at a neutralization degree of 70%, and then mixed with deionized water at a mass ratio of 50:50. Evaluation criteria for water solubility (OK): The solution is uniform and transparent.
[0129] Table 1 shows the test results of the above technical parameters of Examples 1-10 and Comparative Examples 1-3.
[0130] Table 1 Technical parameter test results of Examples 1-10 and Comparative Examples 1-3
[0131]
[0132]
[0133] *“OK” stands for “qualified”, “NG” stands for “unqualified”, and “no data” stands for “not qualified” mainly because the resin is solid at 30℃.
[0134] It can be concluded from Table 1 that the aliphatic amphiphilic dendritic polyesters prepared in the present invention all exhibit amphiphilicity and have significant advantages in terms of solid content and viscosity. Among them, Example 8 has the highest solid content and Example 4 has the lowest viscosity.
[0135] Compared with Comparative Example 1, the aliphatic amphiphilic dendritic polyester prepared in Example 1 of the present invention has a lower viscosity. This is mainly attributed to the fact that aliphatic raw materials have better flexibility than aromatic raw materials and can effectively reduce the viscosity of polyester.
[0136] Compared with Comparative Example 2, the aliphatic amphiphilic dendritic polyester prepared in Example 2 of the present invention exhibits a lower viscosity, which is due to the polymerization process of ring-opening nucleation of anhydride and high-functionality polyols adopted in Example 2. This process reduces the occurrence of side reactions, forms a more compact polyester structure, reduces the molecular radius, and thus effectively reduces the viscosity.
[0137] Compared with Comparative Example 3, the aliphatic amphiphilic dendritic polyester prepared in Example 3 of the present invention not only has good hydrophilicity, but also has low viscosity. This is mainly because the reaction process is adjusted by accurately controlling the acid value of the polyester, reducing the generation of linear polyester by-products, thereby effectively reducing the viscosity of the polyester. In addition, the appropriate acid value also gives the polyester excellent hydrophilicity.
[0138] Through these optimization measures, the polyester product prepared by the present invention is superior to the comparative product in terms of viscosity and solid content, which reflects the significant technical advantages of the present invention in the field of coating resins.
[0139] Evaluation of the application of aliphatic amphiphilic dendritic polyesters in automotive clearcoats
[0140] In order to evaluate the application effect of the aliphatic amphiphilic dendritic polyester prepared by the present invention in automobile clear coat, the following experiment was conducted:
[0141] Sources of materials and reagents:
[0142] KNT939 clear varnish base material, provided by Shanghai Jinlitai Chemical Co., Ltd.;
[0143] Polyester resin WorléePol 1181 / 03, provided by Worlée, Germany;
[0144] Standard color paint panels are provided by Shanghai Jinlitai Chemical Co., Ltd.
[0145] Test method or standard:
[0146] (1) Surface drying time
[0147] The test was carried out in accordance with the national standard GB / T 13477.5.
[0148] (2) Adhesion
[0149] The test was carried out in accordance with the national standard GB / T 9286.
[0150] (3) Gloss
[0151] The test was carried out in accordance with the national standard GB / T 9754.
[0152] (4) Paint film appearance and color
[0153] The test is carried out in accordance with national standards GB / T9761 and GB / T11186.3.
[0154] (5) Gasoline resistance
[0155] The test was conducted in accordance with the national standard GB / T 9274. The test conditions were as follows: immersion in RQ-93 gasoline for 24 hours. Evaluation criteria for the paint film being qualified (OK): no bubbling, wrinkling or peeling; slight discoloration was allowed.
[0156] (6) Oil resistance
[0157] The test was conducted in accordance with the national standard GB / T 9274. Test conditions: immersion in HQ-10 engine oil for 48 hours. Evaluation criteria for the paint film being qualified (OK): no bubbling, wrinkling or falling off; slight discoloration is allowed.
[0158] (7) Alkali resistance
[0159] The test was carried out in accordance with the national standard GB / T 9274. The test conditions were: 23±2℃, 0.1mol / L sodium hydroxide (NaOH) immersion for 24 hours. The evaluation criteria for the paint film being qualified (OK) were: no softening, shedding, dissolution or blistering.
[0160] (8) Acid resistance
[0161] The test was carried out in accordance with the national standard GB / T 9274. The test conditions were: 23±2℃, immersion in 0.05mol / L sulfuric acid (H2SO4) for 24 hours. The evaluation criteria for the paint film being qualified (OK) were: no softening, shedding, dissolution or blistering.
[0162] (9) Water resistance
[0163] The test was conducted in accordance with the national standard GB / T 5209. Test conditions: 40±1℃, immersion in water for 240 hours. Evaluation criteria for paint film qualification (OK): no blistering, wrinkling or peeling; slight discoloration is allowed, and adhesion level 0-1.
[0164] The dendritic polyester and polyester resin Worlée Pol 1181 / 03 of the above Examples 1-3 and Comparative Examples 1-3 were respectively mixed with KNT939 clear varnish base material at a mass ratio of 3:97, stirred evenly using a disperser, and prepared into a coating composition, and the same spraying process was controlled, and the coating composition was sprayed onto a standard color paint plate (KNT939 clear varnish base material was sprayed onto a standard color paint plate as a blank control), and baked at 80°C for 30 minutes to prepare a paint film sample. The test results of the relevant performance indicators of the paint film are shown in Table 2.
[0165] Table 2 Paint film test results
[0166]
[0167]
[0168] It can be concluded from Table 2 that the aliphatic amphiphilic dendritic polyester prepared in the present invention exhibits significant comprehensive performance advantages in the application of automobile clear coats. Specifically, the polyester has a faster drying speed, a higher paint film appearance, and excellent resistance to chemical media such as gasoline resistance, engine oil resistance, acid resistance, alkali resistance, and water resistance. These excellent properties enable the polyester of the present invention to simultaneously meet the requirements of rapid construction and long-lasting protection in the application of automobile clear coats, showing excellent application value.
[0169] Under the guidance of the present invention and the above-mentioned embodiments, it is easy for those skilled in the art to foresee that each raw material or its equivalent substitute, each processing method or its equivalent substitute listed or exemplified in the present invention can realize the present invention, and the upper and lower limit values and interval values of the parameters of each raw material and processing method can realize the present invention, and the embodiments are not listed one by one here.
Claims
1. An aliphatic amphiphilic dendritic polyester, characterized in that: The polyester comprises 60-100 parts by weight of polyester polyol and 0-40 parts by weight of solvent, wherein the polyester polyol comprises the following segments: A first segment provided by a high-functionality polyol component I; A second segment provided by an anhydride compound; A third segment provided by a polyol component II having a molecular weight <500; in, The OH value of the polyester polyol is ≥115KOHmg / g; The acid value of the polyester polyol is greater than or equal to 50KOHmg / g and less than or equal to 290KOHmg / g; The molar ratio of the acid anhydride compound to the high-functionality polyol component I is 3-6, wherein the average functionality of the high-functionality polyol component I is greater than or equal to 3.
2. The aliphatic amphiphilic dendritic polyester according to claim 1, characterized in that The functionality of the polyol component II is greater than or equal to 2.
3. The aliphatic amphiphilic dendritic polyester according to claim 1, characterized in that In the polyester polyol, the content of the high-functionality polyol component I is 6-22 parts, the content of the acid anhydride compound is 28-67 parts, and the content of the polyol component II with a molecular weight less than 500 is 13-53 parts.
4. The aliphatic amphiphilic dendritic polyester according to claim 1, characterized in that The high-functionality polyol component I is selected from at least one of sorbitol, pentaerythritol, xylitol, maltitol, inositol, mannitol, glucose, trimethylolpropane, trimethylolethane, glycerol, arabitol, trimethylolaminomethane, triethanolamine, and β-hydroxyalkylamide; The acid anhydride compound is selected from at least one of hexahydrophthalic anhydride, acetic anhydride, succinic anhydride, maleic anhydride, isophthalic anhydride, trichloroacetic anhydride, trifluoroacetic anhydride, adipic anhydride, tetrahydrophthalic anhydride and maleic anhydride; The polyol component II with a molecular weight of less than 500 is selected from at least one of sorbitol, pentaerythritol, xylitol, maltitol, inositol, mannitol, glucose, trimethylolpropane, trimethylolethane, glycerol, arabitol, trimethylolaminomethane, triethanolamine, ethylene glycol, propylene glycol, butylene glycol, dimethyl-1,3-propanediol, neopentyl glycol, 2-butyl-2-ethyl-1,3-propanediol, 3-hydroxy-2,2-dimethyl-3-hydroxy-2,2-dimethylpropyl propionate, 1,4-cyclohexanedimethanol, trimethylpentanediol, HAA_β-hydroxyalkylamide, isosorbide, 1,2,6-hexanetriol, and hydrogenated bisphenol A.
5. The aliphatic amphiphilic dendritic polyester according to claim 1, characterized in that The solvent is selected from at least one of butyl acetate, xylene, dipropylene glycol methyl ether, propylene glycol methyl ether acetate, propylene glycol methyl ether, 1,3,5-trimethylbenzene, and 1,2,4-trimethylbenzene.
6. A method for preparing the aliphatic amphiphilic dendritic polyester according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: 1) Add the high-functionality polyol component I into the reaction device, slowly heat up to 100-130° C., and stir for 0.5-2 hours; 2) adding the acid anhydride compound to the reaction solution prepared in step 1) in a dropwise manner, and then slowly heating to 120-160° C. for reaction, and testing the acid value at predetermined time intervals until the theoretical acid value is reached; 3) adding the polyol component II with a molecular weight of less than 500 to the reaction solution prepared in step 2), and after the addition, heating the mixture to 150-200° C. at a rate of 8-12° C. / hour and maintaining the temperature, and testing the acid value at predetermined intervals until the target acid value is reached; 4) cooling the reaction solution prepared in step 3) to 100-120° C. and dehydrating the solution at a vacuum pressure of -0.05 to -0.1 MPa for 0.5 to 2 hours; 5) Cooling the reaction solution prepared in step 4) to 80-110° C., adding 0-40 parts by weight of the solvent, stirring evenly, cooling to below 70-90° C., and filtering the material.
7. The method for preparing aliphatic amphiphilic dendritic polyester according to claim 6, characterized in that: In the above step 3), after the polyol component II is added, the temperature is raised to 150-200°C at a rate of 10°C / hour and kept warm; in the above steps 2) and 3), the predetermined time interval for testing the acid value is 1 hour.
8. The method for preparing aliphatic amphiphilic dendritic polyester according to claim 7, characterized in that: The theoretical acid value is calculated by the following method: ((amount of anhydride compound substance*functionality-high-functionality polyol component I*functionality))*56100 / (mass of anhydride compound+mass of high-functionality polyol component I); the target acid value is greater than or equal to 50KOHmg / g and less than or equal to 290KOHmg / g.
9. An automobile clear coat, characterized in that: The invention comprises the aliphatic amphiphilic dendritic polyester described in any one of claims 1 to 5.